2020
DOI: 10.1016/s1473-3099(19)30743-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection predominantly affecting children in Sindh, Pakistan, 2019: a cross-sectional study of an outbreak

Abstract: Background: In April 2019, an HIV screening camp for all ages was established in response to a report of an unusually large number of paediatric HIV diagnoses in Larkana, Pakistan. A cross-sectional study to understand the clinical profile of children who registered for HIV care was performed. Methods: Age-and sex-stratified HIV prevalence among individuals screened was estimated. Data on children who registered for HIV care including clinical history, HIV disease stage, Hepatitis B and C status and CD4 count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Nosocomial outbreaks of HIV infection have previously been reported in Pakistan and other countries, but have mostly been related to a specific health facility and have not been at this scale 5 11 12. In a report of the outbreak, we reported that the proportion of infants with an HIV-positive mother was significantly higher than that among older children, implying that vertical transmission may have contributed to transmission 3. Although there has been an unexpectedly high number of paediatric HIV diagnoses, it is by no means certain that the acquisition of infection by children was recent or from one source.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Nosocomial outbreaks of HIV infection have previously been reported in Pakistan and other countries, but have mostly been related to a specific health facility and have not been at this scale 5 11 12. In a report of the outbreak, we reported that the proportion of infants with an HIV-positive mother was significantly higher than that among older children, implying that vertical transmission may have contributed to transmission 3. Although there has been an unexpectedly high number of paediatric HIV diagnoses, it is by no means certain that the acquisition of infection by children was recent or from one source.…”
Section: Introductionmentioning
confidence: 71%
“…Although the HIV epidemic is mostly limited to key populations, outbreaks in the general population have occurred in previous years 4 8. The outbreak in Larkana, Sindh in 2019 is the largest reported to date and the first time that children have been predominantly affected 3. Although there has undoubtedly been a vigorous effort by the provincial and federal government and other stakeholders to implement an appropriate response to the outbreak, understanding the drivers and the evolution of the HIV outbreak is critical to inform coherent middle-term and long-term strategies to control the HIV epidemic in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2011, after a particularly severe Dengue outbreak, a GPS-enabled mobile application called the Dengue Activity Tracking System (Punjab Information Technology Board) was developed to track suspected and confirmed cases of dengue [ 38 ]. In 2 recent epidemics of the extensively drug-resistant typhoid and human immunodeficiency virus (HIV) in the province of Sindh, geospatial mapping helped considerably with identifying the root causes of the outbreaks and with isolating cases and their spreads [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%